Seismological evidence for Lateral magma intrusion during the July 1978 deflation of the Krafla volcano in NE-Iceland - Einarsson, Pall; Brandsdottir, Bryndis (University of Iceland, Reykjavik, IS, 1978)
The July 1978 deflation of the Krafla volcano in the volcanic rift zone of NE-Iceland was in most respects typical of the many deflation events that have occurred at Krafla since December 1975. Separated by periods of slow inflation, the deflation events are characterized by rapid subsidence in the caldera region, volcanic tremor and extensive rifting in the fault swarm that transects the volcano. Earthquakes increase in the caldera region shortly after deflation starts and propagate along the fault swarm away from the central part of the volcano, sometimes as far as 65 km. The deflation events are interpreted as the result of subsurface magmatic movements, when magma from the Krafla reservoir is injected laterally into the fault swarm to form a dyke. In the July 1978 event magma was injected a total distance of 30 km into the northern fault swarm. The dyke tip propagated with the velocity of 0.4-0.5 m/sec during the first 9 hours, but the velocity decreased as the length of the dyke increased. Combined with surface deformation data, these data can be used to estimate the cross sectional area of the dyke and the driving pressure of the magma. The cross sectional area is variable along the dyke and is largest in the regions of maximum earthquake activity. The average value is about 1200 msup 2. The pressure difference between the magma reservoir and the dyke tip was of the order of 10-40 bars and did not change much during the injection.